Titik Kritis Keamanan Pangan pada Tahap Pengolahan dan Penyajian Beberapa Jenis Minuman Es - Siti Nurjanah; Qonitatin Wafiyah; Winiati P. Rahayu; C. C. Nurwitri (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
In small vendors, iced beverages potentially contain microbiological and chemical hazards. The objective of this study was to identify critical points of hazard during processing and serving steps various types of most popular iced beverages. Based on processing step, there were identified nine types of iced beverages i.e. coconut, grass jelly, sliced fruit, orange, mixed, cendol, juice, blended and flavouring ice. The study was conducted by observation 90 vendors addressed to processing step, utilities, and environ-mental condition at low, middle and high economic scale of vendors. The critical points were determined according to the principles of HACCP. The results showed that more complex of processing step, lower economic scale and poor of facilities caused more critical points. Mixed ice (containing fruits, grass jelly and jelly) that sold at lower economic scale vendor has the most critical points number (11 out of 14), i.e. ice cube, water mixture, syrup, ice washing, ice downsizing, ice storage, fruits and ingredients washing process, fruit and jelly slicing process and storage, and mixing process. On the medium economic scale vendor, there were 1-3 critical points number and on the highest economic scale there was only one critical point number which was in the mixing process.